Response of the Geospace System to the Solar Wind Dynamic Pressure Decrease on 11 June 2017: Numerical Models and Observations. Issue 4 (10th April 2019) - Ozturk, Dogacan S.; Zou, Shasha; Slavin, James A.; Ridley, Aaron J.
Abstract: On 11 June 2017, a sudden solar wind dynamic pressure decrease occurred at 1437 UT according to the OMNI solar wind data. The solar wind velocity did not change significantly, while the density dropped from 42 to 10 cm −3 in a minute. The interplanetary magnetic field B Z was weakly northward during the event, while the B Y changed from positive to negative. Using the University of Michigan Block Adaptive Tree Solarwind Roe Upwind Scheme global magnetohydrodynamic code, the global responses to the decrease in the solar wind dynamic pressure were studied. The simulation revealed that the magnetospheric expansion consisted of two phases similar to the responses during magnetospheric compression, namely, a negative preliminary impulse and a negative main impulse phase. The simulated plasma flow and magnetic fields reasonably reproduced the Time History of Events and Macroscale Interactions during Substorms and Magnetospheric Multiscale spacecraft in situ observations. Two separate pairs of dawn‐dusk vortices formed during the expansion of the magnetosphere, leading to two separate pairs of field‐aligned current cells. The effects of the flow and auroral precipitation on the ionosphere‐thermosphere (I‐T) system were investigated using the Global Ionosphere Thermosphere Model driven by simulated ionospheric electrodynamics. The perturbations in the convection electric fields caused enhancements in the ion and electron temperatures. This study shows that, like the well‐studied sudden solar wind pressure increases, sudden pressure decreases can have large impacts in the coupled I‐T system. In addition, the responses of the I‐T system depend on the initial convection flows and field‐aligned current profiles before the solar wind pressure perturbations. Key Points: The decrease in the solar wind dynamic pressure led to two separate pairs of oppositely rotating vortices in the dawn and dusk FACs accompanied each magnetospheric vortex and altered the ionosphere convection patterns Joule heating increased in the regions sandwiched by the perturbation FACs, leading to increased ion temperatures